2012
DOI: 10.1136/vr.100051
|View full text |Cite
|
Sign up to set email alerts
|

Modelled impacts of badger culling on cattle TB in a real area with geographic boundaries

Abstract: As a part of bovine tuberculosis eradication strategy, the Welsh Government has proposed a badger cull in a defined area in and around North Pembrokeshire, and has published information on herd densities and incidence levels within and close to the area. In the present study, three sets of previously published data relating the impact of badger culling inside and around previous culling areas to distances from culling area boundaries have been used to model possible impacts of the proposed cull, taking account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Prior to the RBCT it was felt that the results from several badger removal operations in England and Ireland demonstrate the importance of establishing adequate experimental controls, as some other unidentified factor could have been responsible for changes in herd breakdown rates 37 . Equally, most key studies cited in government policy that are subsequent to the RBCT that commenced in 1998, are derivative of it and use the RBCT model from 2006 to achieve their results and interpretations (For example studies reported by Jenkins et al 24 , Bielby et al 25 , Vial & Donnelly 26 , Vial, et al 27 , Fenwick 28 , McCulloch et al 29 and Donnelly and Nouvellet 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the RBCT it was felt that the results from several badger removal operations in England and Ireland demonstrate the importance of establishing adequate experimental controls, as some other unidentified factor could have been responsible for changes in herd breakdown rates 37 . Equally, most key studies cited in government policy that are subsequent to the RBCT that commenced in 1998, are derivative of it and use the RBCT model from 2006 to achieve their results and interpretations (For example studies reported by Jenkins et al 24 , Bielby et al 25 , Vial & Donnelly 26 , Vial, et al 27 , Fenwick 28 , McCulloch et al 29 and Donnelly and Nouvellet 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much subsequent investment in research has assumed that the coe cient value (ie -0.207) for the proactive culling parameter in the log linear Poisson model is a true re ection of the expected effect size for reduction in incidence in response to culling. There are many studies and reports which rely on this 19,[23][24][25][26][27][28][29] . The view that the RBCT analysis represented a 'strong evidence base involving experimental studies or eld data collection on bTB with appropriate detailed statistical or other quantitative analysis.'…”
Section: Discussionmentioning
confidence: 99%
“…Different aspects of the studies are often reported without reference to their wider context. Additionally, the original conclusions of the RBCT have been debated (see for example Fenwick ); this has found its way into the media, adding to the lack of a clear evidence base on which to frame disease control arguments.…”
Section: Discussionmentioning
confidence: 99%